2011
DOI: 10.5586/asbp.2011.029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of α-aminooxyacetic acid on the level of polyamines, anthocyanins and photosynthetic pigments in seedlings of common buckwheat (Fagopyrum esculentum Moench)

Abstract: The present paper discusses the effects of α-aminooxyacetic acid (AOA) on contents of polyamines, anthocyanins, photosynthetic pigments and phenylalanine ammonia-lyase activity in seedlings of common buckwheat (Fagopyrum esculentum Moench). AOA clearly decreased light-induced formation of anthocyanins and inhibited PAL activity in buckwheat hypocotyls, although a slight stimulatory effect on anthocyanins content in buckwheat cotyledons was observed. AOA declined the contents of chlorophylls a and b, and total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…This was probably due to other activities of ethylene inhibitors in plant metabolism. AOA has also been found to be an inhibitor of phenylalanine ammmonia lyase (PAL), the first enzyme in the phenylpropanoid pathway (Horbowicz et al, 2011). The study on Arabidopsis indicated that AVG had a negative effect on ACC synthase activity, and also reduced the endogenous IAA content (Soeno et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This was probably due to other activities of ethylene inhibitors in plant metabolism. AOA has also been found to be an inhibitor of phenylalanine ammmonia lyase (PAL), the first enzyme in the phenylpropanoid pathway (Horbowicz et al, 2011). The study on Arabidopsis indicated that AVG had a negative effect on ACC synthase activity, and also reduced the endogenous IAA content (Soeno et al, 2010).…”
Section: Discussionmentioning
confidence: 99%